Multi-spectroscopic investigation on the inclusion complexation of α-cyclodextrin with long chain ionic liquid. (May 2020) - Banjare, Manoj Kumar; Behera, Kamalakanta; Banjare, Ramesh Kumar; Pandey, Siddharth; Ghosh, Kallol K.
Abstract: Host-guest interaction of ionic liquid (IL) 1-decyl-3-methylimidazolium tetrafluoroborate [Dmim][BF4 ] within α-cyclodextrin (α-CD) has been studied by different spectroscopic techniques and our investigated system is significant in the field of supramolecular chemistry and medicine. Benesi-Hildebrand correlation is used to study the stoichiometry of the host-guest complexation. Here concurrence with FT-IR and dynamic light scattering (DLS) results, it is shown that α-CD interacts with [Dmim][BF4 ], induces compositional and structural changes. Characterization of the [Dmim][BF4 ]-α-CD inclusion complex (IC) by 1 H NMR spectroscopy provided information about the complexation among the [Dmim][BF4 ] and α-CD molecules and the structure of the ICs. 1 H NMR results confirm the formation of inclusion complex (IC) while UV–vis spectroscopy, DLS and FTIR studies show development of IC with 1:1 stoichiometry. The present study can be highly applicable in the fields of pharmaceutical science, supra-molecular chemistry and material science. Graphical abstract: Host-guest interaction of 1-decyl-3-methylimidazolium tetrafluoroborate [Dmim][BF4 ] within α-cyclodextrin (α-CD) have been investigated using Uv–vis, DLS, FTIR and 1 H NMR spectroscopy. The formation of ICs with cyclodextrin, variety of non-covalent forces i.e., van der Wall forces, hydrophobic interaction and dipole movement are responsible. Image 1 Highlights: This method was established to calculate the binding constant. This approach is appropriate for all types of guest molecules tested. UV–vis spectra increase by α-CD concentration ICs formation. The 1:1 stoichiometric ICs is confirmed by using the BH equation. The DLS, FTIR and 1 H NMR analysis confirmed the ICs formation.